Establishing genetic diagnosis of intellectual disability in children: diagnostic yield of various genetic approaches - Kalibataitė, Irma; Rutkauskas, Vilius; Preikšaitienė, Eglė; Kučinskas, Vaidutis (Acta medica Lituanica, 2013)
Background. The aim of our investigation was to examine aetiology of intellectual disability / developmental delay (ID / DD) in children referred to the Centre for Medical Genetics at the Vilnius University Hospital Santariskiu Clinics during 2009 and to evaluate the diagnostic yield of current genetic approaches. Materials and methods. In a retrospective investigation, medical records of 217 patients younger than 18 years of age were reviewed with a focus on the family history and pedigree, personal history, physical examination, imaging and laboratory diagnostics. Patients with established genetic diagnosis were compared with cases without identified disorders. Aetiological structure of all cases was explored, as well as factors influencing the diagnosis of genetic predisposition and the yielding of the genetic methods for investigation of patients with ID or DD available in 2009. Results. Genetic diagnosis was established for 88 (40.5%) patients. The diagnostic yielding of conventional karyotyping was 18%, molecular karyotyping 12.4%, metabolic testing 4.1%, FISH 2.3%, molecular genetics 0.9%, in 2.8% of patients the fetal alcohol syndrome was diagnosed. Conclusions. Currently the most effective are conventional karyotyping and molecular karyotyping techniques, showing that chromosomal alterations are the most common cause of ID / DD. Mostly the diagnosis is established in severe cases of ID / DD with congenital anomalies and dysmorphic features. Metabolic testing is especially effective if suggestive clinical features of metabolic disorders are present. The low yielding of molecular genetics methods indicates the need of their integration into diagnostics of ID / DD in Lithuania.
Keywords: children intellectual disability; aetiology; genetic approaches